Social media rhetoric: an analysis of companies marketing probiotics on Facebook and Twitter - Young, Alicia R. (University of Wisconsin--Stout, 2019)
The purpose of this research study was to evaluate the message and methods that Culturelle, Garden of Life, and Renew Life dietary supplement companies use to market probiotic products through social networks. The goal was to identify the rhetorical strategies to educate consumers about the health benefits from science-based testing, build trust with followers that could influence buying choices. The analysis concludes with suggestions how companies can engage followers, educate consumers regarding the benefits and risks of probiotics, and advertise products. The research question is: What are the digital rhetorical strategies probiotic brands use to educate, inform, and influence purchasing decisions? A qualitative research study design was selected for this topic. A total of 254 social network post updates were analyzed for three dietary supplement companies. Social network posts were divided into thematic categories according to textual and visual elements and post analytics were compared with each company (likes, comments, shares) to evaluate engagement and if content was consistent with brand identity. The results revealed differences in post frequency, quality, consistency, and health topics among the companies. This study contributes to understanding the digital rhetoric strategies to market dietary supplements to a wide and varied audience.
Keywords: Social media